2019
DOI: 10.1088/1755-1315/370/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of lobster larvae (Panulirus spp.) from the Indonesian Eastern Indian Ocean

Abstract: Lobster fisheries play an important role in the development of Indonesian fisheries management. The tropical lobster genus Panulirus has high species diversity in the Indonesian Eastern Indian Ocean. The Indonesian government has designated lobster fisheries as one of the types of fisheries requiring special attention in 11 of the Fisheries Management Areas in the Republic of Indonesia (FMARI). Each management area has specific ecological characteristics and may have unique lobster species richness. Studies on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
7
0
2
Order By: Relevance
“…The growth pattern of ornate spiny lobster was negatively allometric, so carapace length increases faster than ornate spiny lobster weight. Negative allometric growth patterns of ornate spiny lobster in Sebatik Island waters is possible due to abiotic factors from a high level of pressure from the marine environment where they live, with dominant human activities, functional gonad maturity, and oceanographic processes 24,25 . As a comparison from other research on ornate spiny lobster growth patterns, data from Sorong waters shows a negative allometric pattern 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth pattern of ornate spiny lobster was negatively allometric, so carapace length increases faster than ornate spiny lobster weight. Negative allometric growth patterns of ornate spiny lobster in Sebatik Island waters is possible due to abiotic factors from a high level of pressure from the marine environment where they live, with dominant human activities, functional gonad maturity, and oceanographic processes 24,25 . As a comparison from other research on ornate spiny lobster growth patterns, data from Sorong waters shows a negative allometric pattern 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The difference in b-value variance is affected by the dimensions of carapace length and weight levels of each species. Still, it may also be affected by several factors, such as food availability, water quality, sexual, gonad maturity level, and habitat well-being 24,25,27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…lobster larva's attractor material is unsame in different locations. Waring is main material, for example was widely used by fishermen in the Trenggalek, Banyuwangi and Lombok areas [ Previous study found that there were six species of puerulus inhabit Eastern Indian Ocean of East Java [12]. From the research, there were 4 species of captured puerulus species, including Ornate puerulus, Scalloped puerulus, Painted puerulus and Pronghorn puerulus.…”
Section: Species Composition At 20 Meter Of Depthmentioning
confidence: 96%
“…The SeaLifeBase distribution is limited to four countries/territories: China, Hong Kong, Taiwan and Thailand (Palomares & Pauly, 2021). At least eight species are reported from Indonesia: Panulirus homarus, P. ornatus, P. penicillatus, P. longiceps, P. polyphagus, P. versicolor, P. daypus, and P. femoristriga (Wahyudin et al, 2016;Teteleptal et al, 2017;Setyanto et al, 2019). Reports of declining stocks (Teteleptal et al, 2017) indicate a need for sustainable fisheries management of this genus.…”
Section: Economically Important Decapod Crustaceansmentioning
confidence: 99%